PENGARUH MODEL CONTEXCTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN LITERASI SAINS SISWA MATA PELAJARAN IPA KELAS IV SDN PEPE SEDATI-SIDOARJO - Ni’mah, Jazilah Nailatun; Murni, Arie Widya (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2026)
This research is based on the lack of interest of students in science literacy. So that the abilities possessed by students still do not meet the indicators determined by the researcher. Basically, this research aims to analyze the effect of the Contextual Teaching and Learning (CTL) model on the scientific literacy abilities of fourth-grade students of SDN PEPE Sedati-Sidoarjo. The type of research is quantitative research with a quasi-experimental design experimental method with a pretest-posttest control group design type. The sample of this research is class 4 of SDN PEPE Sedati with details of 60 students, namely class IV B 30 students as the experimental class and class IV A 30 students as the control class. The data analysis technique in this study uses a science literacy test. The results of the study produced an average pretest score of the experimental class of 46.1 and a posttest of 80.5, while the average pretest score of the control class was 60 and a posttest of 66.4. The average N-Gain value in the experimental class was 63% (medium category), while in the control class it was 16% (low category). The t-test showed a significant difference between the experimental and control classes with a significance value of 0.000 < 0.05. Thus, it can be concluded that the application of the CTL model can significantly improve students' scientific literacy skills